Analysis of Collaborative Governance in Realizing Sustainable: JEL Classification: H77, L83, O18, Q56, R58 - Lushinta Hanifa Anantaningrum; Cahyanti, Miftachul; Yanuar, Fido Aziz; Zaskia, Nabilla Anggun; Primar, Septha Novita Candrawati (Newinera Publisher, 2025)
Amidst global challenges, sustainable tourism has become a key strategy to support SDG Goal 8, namely decent work and economic growth. This study focuses on the revitalization of Surabaya's Old Town as a case study, which has successfully increased tourism and economic appeal. The objective is to examine the implementation of collaborative governance and the role of stakeholders in realizing sustainable tourism. The method used is a qualitative approach with phenomenology to explore the experiences of stakeholders. Data analysis is supported by ATLAS.ti 9 software, which facilitates coding, data comparison, and identification of complex relationships between factors. The results show that collaborative governance is an effective approach. Its implementation includes three main elements of Emerson's theoretical framework: principled engagement, shared motivation, and shared action capacity. Principled engagement is realized through open communication, collaboration between OPDs, and regular forums such as FGDs. Shared motivation is strengthened by trust, legitimacy, and commitment between parties, including academics involved in the preparation of the RTBL. Joint action capacity is demonstrated through the collaborative leadership of the Mayor of Surabaya and structured procedural arrangements. In conclusion, the implementation of collaborative governance contributes significantly to sustainable tourism development in line with SDG 8. This contribution includes an increase in tourist visits, local economic growth, job creation, cultural preservation, and community empowerment. This research proves that collaborative governance is an effective approach to realizing inclusive, productive, and sustainable tourism.